Comment être artiste, femme et autochtone au Canada ? Du stigmate à son renversement dans l'art contemporain - Goyon, Marie (Sociologie de l'Art, 2011)
Résumé Cet article analyse les usages de savoir-faire genrés dans la création contemporaine autochtone canadienne. Ils sont considérés dans leur caractère doublement situé, culturel et sexué. Comment analyser les usages des savoir-faire dits « féminins » (couture, broderie) dans les œuvres de plasticiennes contemporaines ? La réflexion s’appuie sur l’étude des trajectoires biographiques et des œuvres de trois artistes canadiennes autochtones. Une double stigmatisation de ces artistes, marquée de stéréotypes ethniques et genrés, est repérée dans les conditions d’exposition de leurs œuvres en tant qu’autochtones (musées d’ethnologie) et en tant que femmes (musées locaux, statut non professionnel des créatrices). Leurs démarches pourront être qualifiées de postcoloniales, interrogeant les frontières normatives entre arts « majeurs » et arts « mineurs », ainsi que la place des arts « premiers » et des femmes créatrices dans l’histoire de l’art
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; art contemporain; art textile; artisanat; artistes autochtones; arts; arts textiles; canada; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; travaux d'aiguilles

Representing the Black female subject in western art - Nelson, Charmaine (Routledge studies on African and Black diaspora, 2010)
Nelson analyzes not only how, where, why and by whom black female subjects have been represented in Western art, but also what the social and cultural impacts of the colonial legacy of racialized Western representation have been. She poses questions about the concepts of production, the consequences of comsumption and more
Keywords: afro-féminisme; approches et analyses; arts; cours; discipline; féminisme afroaméricain; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; système colonial; systèmes d'oppressions; thématiques

With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques